Defense enzymes triggered by Exobasidium vexans Massee induce resistance in tea plants - and R. DAS-BISWAS, B.N. CHAKRABORTY*, M. SHARMA (Indian Phytopathology, 2005)
Involvement of defense related enzymes such as chitinase (CHT), b-1,3-glucanase (bGLU) and peroxidase (POX) in developing resistance in tea plants against Exobasidium vexans causing blister blight disease was evaluated. Among the ten tea varieties tested against E. vexans, B-668 and T-135 were found to be most susceptible while P-1258 and TV-26 were resistant under identical conditions. Screening for resistance of these varieties towards E. vexans based on plate trapped antigen (PTA) format of ELISA using polyclonal antibodies of the pathogen (PAb-EV) also confirm the results. Changes in the levels of enzyme activities were noticed in tea varieties exhibiting compatible and incompatible interactions against E. vexans. Disease free leaf samples exhibited greater accumulation of CHT and bGLU than infected ones. However, considerable increase in POX activity was evident in plants showing resistant reaction against E. vexans after overcoming the disease in the field condition. Time course accumulation of defense enzymes in tea plants triggered by inoculation with E. vexans showed a general increase in CHT and bGLU within 24 h of inoculation whereas the activity of POX increased 48 h post-inoculation. Elicitation of these defense enzymes was also evident in plants induced with salicylic acid (SA). Induced resistance occurs when an early synergistic increase in CHT and bGLU activity is coupled with POX.